Small GTPase ARL4C Associated with Various Cancers Affects Microtubule Nucleation - Evgeniia Ulas; Ilya Brodsky; Anton Burakov (Biomedicines)
Background/Objectives: The changes in the level of small GTPase ARL4C are associated with the initiation and progression of many different cancers. The content of ARL4C varies greatly between different tissues, and the induction of ARL4C expression leads to changes in cell morphology and proliferation. Although ARL4C can bind alpha-tubulin and affect intracellular transport, the role of ARL4C in the functioning of the tubulin cytoskeleton remained unclear. The aim of the present work is to study this role; Methods: The cells of the following lines were used for the experiments: HeLa (human cervical carcinoma), MCF7 (human breast cancer), U2OS (human osteosarcoma), Vero, BS-C-1, and COS7 (African green monkey kidney). The receptor activation by agonists followed by the preparation of cell lysates, electrophoresis, and immunoblotting, as well as cell fixation and immunofluorescent staining, were used to assess endogenous ARL4C/ABCA1 levels and the microtubule network morphology. The microtubule regrowth technique was performed to estimate the rate of microtubule nucleation, and the overexpression of different ARL4C constructs was used to affect ARL4C activity in the cells; Results: We showed that the changes in the endogenous ARL4C level or the ARL4C activity alter the microtubule nucleation process in the cells; Conclusions: small GTPase ARL4C may serve as one of the regulators of the microtubule nucleation process both in normal and cancer cells.